Solving self-interference issues in a Full-Duplex radio transceiver - Miguel Franco-Martinez; Francisco-Javier Martinez-Alonso; R. López-Valcarce (2nd XoveTIC Conference, 2019)
Most wireless devices transmit and receive at different spectrum frequency bands. This approach is no longer optimal due to increasing electromagnetic exhaustion. Besides, interference among all present and future working services should be negligible. A full-duplex scheme using the same band for simultaneous uplink and downlink is a huge step towards solving this issue. However, sharing the same frequency band involves a large interference of transmitted signal over received signal. To fix this problem, we propose the usage of a hybrid multistage cancellation system, consisting of an analog cancellation setup at RF frequencies and a baseband digital cancellation stage.
Keywords: adaptive signal processing; full-duplex; winter